PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN CV LAUTAN REZEKI PEKANBARU - Yunita Sari; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of compensation and work discipline simultaneously and partially on the performance of employees of CV. Lautan Rezeki Pekanbaru. The data in this study were obtained by distributing questionnaires to 40 employees. After the data was collected, it was analyzed using descriptive statistics and regression analysis with the help of the SPSS application through reliability, validity, simple regression analysis, multiple regression analysis, F test (simultaneous), t test (partial) and the coefficient of determination.The results showed that compensation and work discipline simultaneously and partial have a significant effect on the performance of employees of CV. Lautan Rezeki Pekanbaru. Keywords: Compensation, Employess Performance, Work Discipline